Advantages of using ohmic heating in Dulce de Leche manufacturing. (October 2020) - Silva, Ramon; Rocha, Ramon S.; Guimarães, Jonas T.; Balthazar, Celso F.; Pimentel, Tatiana C.; Neto, Roberto P.C.; Tavares, Maria Inês B.; Esmerino, Erick A.; Duarte, Maria Carmela K.H.; Freitas, Mônica Q.; Silva, Paulo Henrique F.; Cappato, Leandro P.; et al.
Abstract: Ohmic heating (OH, 0, 2, 4, 6, 8, or 10 V cm −1, 72 °C/15 s, 60 Hz) at Dulce de leche processing was investigated. The equipment consisted in an ohmic heating chamber, and rectangular 316 stainless steel electrodes positioned 10 cm apart. OH-treated milk resulted in improvements in the quality parameters of Dulce de leche, with a decrease in energy expenditure (69.85–141.86 vs 1260 kJ) and hydroxymethylfurfural (HMF) levels (7.64–8.54 vs 9.53 μmol L −1 ), an increase in product homogeneity, and formation of volatile compounds important for the sweetness of Dulce de leche (butanoic acid and 2-furan methanol). In addition, the physicochemical composition, fatty acid profile, and health indices (atherogenic, thrombogenic, desired fatty acids, and hypercholesterolemic saturated fatty acids) of the products remained without changes. In particular, the use of higher electric field (> 6 V cm −1 ) led to a 14–78% decrease in process time, and improved volatiles profile. OH has proven to be a suitable technology for milk treatment, resulting in improvements in the quality parameters of Dulce de leche with positive impact at the process time and energy expenditure. Industrial relevance: The Dulce de Leche processing is characterized by long cooking times to acquire its typical characteristic color and flavor. Normally, it is used pasteurized milk as raw material. Ohmic heating decreased the total time of processing in Dulce de leche manufacturing, providing an economy at the in the energy costs without significant change at the quality parameters of the final product. Highlights: Dulce de leche prepared with milk submitted to Ohmic Heating treatment; OH decreased energy expenditure, processing time and hydroxymethylfurfural levels; OH had no effect on proximate composition and fatty acid profile of Dulce de leche; OH resulted in products with increased number of important volatile compounds.